Management of Primary Tooth in Agenesis of Lateral Incisor of Upper Jaw - Amelia Nurmaldiana; Jeffrey Jeffrey (e-GiGi, 2022)
Abstract: Agenesis is commonly found in maxillary lateral incisors with a relative high preva-lence. We reported a case of agenesis of the lateral upper incisor associated with dental caries. A 20-year-old man came to Unjani Dental Hospital with a complaint of cavities in the left upper incisor. His only complaint was lack of confidence due to the dental caries; no complaint of pain. At the first visit, anamnesis and clinical examination were performed on him. Oral hygiene was good. Tooth 63 had moderate caries, vital, no mobility, and the percussion and pressure tests were negative. Radiography examination revealed agenesis of tooth 22. This case was confirmed as reversible pulpitis of tooth 63, associated with agenesis of tooth 22. First treatment was restoration of the labial surface of tooth 63 using restoration material with the same color (composite). Â At the second visit a week after, the examination revealed positive vitality and no more complaint. The purposes of restorative treatment in this patient were to repair caries damage, protect and prevent further damage of the pulp and other tooth structures, reduce symptoms and pain, restore the tooth function, improve esthetics, support good oral hygiene, and maintain the tooth space and arch. In conclusion, primary teeth can be preserved as a substitute for agenesis teeth. Successfull treatment depends on the collaboration between the dentist and the patient.Keywords: agenesis; primary teeth; lateral incisivus lateral of maxillaÂ Abstrak: Umumnya agenesis dijumpai pada gigi insisivus lateral rahang atas dengan prevalensi yang cukup tinggi. Kami melaporkan sebuah kasus agenesis yang terjadi pada gigi insisivus lateral atas disertai karies gigi. Seorang laki-laki berusia 20 tahun datang ke Rumah Sakit Gigi dan Mulut (RSGM) Unjani dengan keluhan adanya gigi berlubang pada gigi depan kiri atas. Pasien tidak mengeluhkan rasa nyeri, hanya merasa kurang percaya diri karena gigi tersebut tampak berlubang. Pada kunjungan pertama pasien dilakukan anamnesis dan pemeriksaan klinis. Didapatkan oral hygiene baik. Gigi 63 mengalami karies media, vital, tidak terdapat kegoyangan, serta tes perkusi dan tes tekan negatif. Pada hasil pemeriksaan radiografi tidak didapatkan adanya benih gigi 22. Diagnosis untuk kasus ini ialah pulpitis reversibel gigi 63 disertai agenesis gigi 22. Perawatan pertama berupa restorasi pada permukaan labial gigi 63 menggunakan bahan restorasi sewarna gigi yaitu komposit. Pasien diminta untuk kembali kontrol setelah satu minggu. Saat kontrol dilakukan pemeriksaan vitalitas gigi dengan hasil positif serta tidak ada keluhan dari pasien. Tujuan perawatan restoratif pada pasien ini ialah memperbaiki kerusakan jaringan akibat karies, melindungi dan mencegah kerusakan pulpa dan struktur gigi, mengurangi gejala dan nyeri, mengembalikan fungsi, meningkatkan estetik, mendukung kebersihan mulut yang baik, dan mempertahankan ruang serta lengkung gigi. Simpulan kasus ini ialah gigi sulung dapat diper-tahankan sebagai pengganti gigi yang mengalami agenesis. Keberhasilan perawatan tergantung pada koordinasi antara dokter gigi dan pasien.Kata kunci: agenesis; gigi sulung; insisivus lateral rahang atas